The Principle of Control Non Primary Gun System of the Indonesian National Army Protect Soldiers - Said Gunawan (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2020)
This study aims to analyze and discover the principle of non-defense equipment regulation as a legal protection effort for members of the Indonesian Armed Forces and to reconstruct non-defense system arrangements in the context of legal protection for members of the TNI based on the value of certainty and justice with dignity. The research method in this research is descriptive juridical using statute approach, conceptual approach, analytical approach, philosophical approach and case approach. These approaches can be combined. The results of the research show that first, the principle of non-defense system regulation is subject to Law Number 34 of 2004 concerning the Indonesian National Army, especially the principle of civilian supremacy. The principle is only included in the basis of consideration. Does not specifically regulate the general provisions and body of the regulation regarding the terms and meaning of non-defense equipment and has not become one of the main tasks of the TNI in non-war military operations. Second, reconstruction of the value of alusista and non-alusista abuse must be subject to sanctions. Keywords: Defense Equipment; Indonesian National Army; Defense.